The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5851/kosfa.2019.e19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Storage-Temperature Combinations on Longissimus dorsi Quality upon Sous-vide Processing of Frozen/Thawed Pork

Abstract: This study investigated the effect of storage state (chilled state on sous-vide, CS; frozen state without thawing on sous-vide, FS; and frozen/thawed states on sous-vide, TS) and sous-vide cooking temperature (65°C and 72°C) on the longissimus dorsi muscle quality of pork. FS showed a higher moisture content than that of CS and TS (p<0.001), whereas both FS and CS showed higher expressible moisture loss than that of TS (p<0.001). FS showed a lower cooking loss (p<0.001) than that of CS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The non-significant effects of storage temperature on tenderness in the current study also are in line with a previous study by Fernandes et al [27]. Similar results were also reported by Ji et al [36] in pork meat. However, it has been reported that sensory evaluation of freeze/thawed beef meat was rated less tender compared with chilled meat, which might be due to the fluid loss during thawing, and reduced hydration of muscle fibers leads to a reduced tenderness [2,3].…”
Section: Effects Of Different Storage Temperature and Storage Duratiosupporting
confidence: 93%
“…The non-significant effects of storage temperature on tenderness in the current study also are in line with a previous study by Fernandes et al [27]. Similar results were also reported by Ji et al [36] in pork meat. However, it has been reported that sensory evaluation of freeze/thawed beef meat was rated less tender compared with chilled meat, which might be due to the fluid loss during thawing, and reduced hydration of muscle fibers leads to a reduced tenderness [2,3].…”
Section: Effects Of Different Storage Temperature and Storage Duratiosupporting
confidence: 93%
“…Most researchers have studied only the influence of different combinations of a single temperature and time in sous vide processing on the quality attributes of beef [ 11 , 12 , 13 ], pork [ 14 ], turkey [ 15 ], and chicken [ 16 , 17 ]. On the other hand, several authors reported using additional pretreatments such as freezing technology [ 12 ] or thawing [ 18 ] before sous vide to achieve meat tenderization. Botinestean et al [ 12 ] found that short-term freezing of beef steaks at −20 °C resulted in comparable shear force, hardness, and chewiness values with sous vide cooking alone.…”
Section: Introductionmentioning
confidence: 99%
“…Botinestean et al [ 12 ] found that short-term freezing of beef steaks at −20 °C resulted in comparable shear force, hardness, and chewiness values with sous vide cooking alone. Ji et al [ 18 ] concluded that freeze-thawing and freezing applied prior to sous vide significantly decreased the shear force of pork meat. However, from an economic perspective, these attempts do not seem feasible because they impose extra processing costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that frozen storage temperatures or thawing methods could lead to the formation of ice crystals, affecting physicochemical and sensory characteristics of meat (Carlucci et al, 1999;Lagersted, 2008;Vieira et al, 2009;Bueno et al, 2013;Huang et al, 2013). Most studies on the sensory analysis of meat freezing have focused on meat flavor and texture (Zhang et al, 2019;Ji et al, 2019); however, no studies have used the Quantitative Descriptive Analysis (QDA®) to describe the effects of freezing/thawing processes on sensory attributes of meat, such as appearance, aroma, flavor, and texture for a comprehensive sensory assessment.…”
Section: Introductionmentioning
confidence: 99%